Promoting a Gender-Sensitive Learning Environment among Primary and Secondary School Leaders in Zimbabwe - Muzvidziwa, Irene (Bloomsbury Academic, 2022)
While there has been a marked increase in research on women and management in many countries, not much has been documented on gender and school leadership in Zimbabwe. On the other hand, ‘Zimbabwe has made significant strides in amending and enacting legislation . . . to advance gender equality and equity objectives’ (MWAGCD 2017) . Because of globalization, environmental changes and many other factors, there are new demands for schools and school leaders to ensure progress in the teaching and learning of pupils. In 2017, the Ministry of Women Affairs, Gender and Community Development (MWAGCD) initiated the National Gender Policy with a vision to build a gender just society. The policy objective was ‘To ensure equal access to education for boys and girls’ (MWAGCD 2017: 23) . The policy strategies were aimed at creating an enabling environment for accessing and retaining girls at secondary level; promote equal access...